PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN LEMBAR KERJA PESERTA DIDIK TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK FASE F PADA MATERI SISTEM PERNAPASAN DI SMA NEGERI 1 LENGAYANG - Nia Sefri Yeni; Helendra; Zulyusri; Fitri Olvia Rahmi (LPPM Universitas Cipta Mandiri, 2025)
Beginners ought to have twenty first century competencies, definitely one among that's the capability to suppose critically. The results of the initial observation of phase F at Lengayang 1 State Senior High School were 29.40% and were included in the non-critical category. The reason lies in the model that is carried out, which is not optimally carried out, therefore, it is important to make efforts to improve critical thinking skills through the Problem Based Learning model assisted by Student Worksheets. The cause of this study turned into to determine the impact of the PBL version assisted through LKPD at the critical thinking skills of phase F students on respiratory system cloth at SMA Negeri 1 Lengayang. This research is an experiment. The design used is randomized control-group posttest only design. The populace on this look at were all phase F students. Sample determination using purposive sampling approach. The studies pattern became received, namely class XI.F1 as the experimental class and class XI.F3 as the control class. The research instrument is a 12-item essay with an evaluation primarily based on critical thinking skills indicators. The experimental class research results have been higher than the control class with the average posttest rating of the experimental class (85,13%) and the control class (56,8%). Data processing using the independent sample t-test obtained a significance of 0.001 < 0.05, this indicates that the intervention in the experimental class had a significant effect compared to the control class. Based on this, it can be concluded that the PBL model is assisted by LKPD has a tremendous effect at the critical thinking skills of phase F college students at the material of the respiratory system at SMA Negeri 1 Lengayang.